(untitled) (Daffodil International University Journal of Science and Technology, 2011)
This paper proposes an efficient low update latency handover scheme for Proxy Mobile IPv6 (PMIPv6)-a Network-based mobility management protocol. The major aspect that introduces high latency during Mobile Node (MN) handover between Mobile Access gateways (MAGs) of the same PMIPv6 domain has been analyzed. The analysis included MN profile acquirement by MAG agent and handover process between MAG agents. From this analysis, an improved solution that optimizes the handover delay has been provided. The solution has been verified by simulation in Network Simulator 2(NS2). Keywords: PMIPv6; Handover Delay; NS2; FMIPv6; MIPv6; PMIPv6_Ex DOI: http://dx.doi.org/10.3329/diujst.v6i1.9328 DIUJST 2011; 6(1): 9-16